Tallasa Kamase-Masea: Green Citizenship Construction and Green Law in Pasang ri Kajang to Sup SDGs Indonesia - Haris, Hasnawi; Ridhoh, M. Yunasri; Muhtar, Muhtar (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
This study aims to construct the concept of Green Citizenship and Green Law value-based Tallasa Kamase-Masea in Pasang ri Kajang in order to support Sustainable Development Goals (SDGs) Indonesia. The background of this research is based on the urgency ecological reform that relies not only on formal regulations, but also on ecological citizenship awareness and laws based on local wisdom. By using the approach qualitative and legal hermeneutics and ethnography, this study explores the meaning, symbol, and practice the ecology of the Kajang indigenous community in Bulukumba Regency, South Sulawesi. Results research shows three main things: (1) Tallasa Kamase-Masea describing the paradigm ecological, placing humans and nature in an egalitarian cosmic relationship; (2) values the aforementionned become the conceptual basis for Green Citizenship, namely citizenship active, reflective, and responsible for environmental sustainability; as well as (3) Pasang ri Kajang serves as Green Law customary-based, which regulates the ethics of ecological interactions through the principles of simplicity, non-exploitation, and respect for natural habitats. These findings imply the strengthening of environmental law policies and education on citizenship with an ecological perspective as a strategic foundation for achieving SDGs at the local and national levels.